Sex ratio of children born to Orthopedic surgeons in Jordan: a National Cross-sectional study. - Alananzh, Mohammad; Aldahamsheh, Osama; Alkhreisat, Mohammad; Al-Qudah, Ala' Khaled; Al-Omari, Jamal A.K; Alkhatatba, Ayman; Badrsawi, Mariam; Abusada, Wala'a Mohammad; Algaafari, Hashem Mohammed (Journal of Neonatal Surgery, 2025)
The secondary sex ratio at birth is typically stable worldwide, but some evidence suggested that radiation exposure among surgeons may influence offspring ratio. This national cross-sectional survey of 92 orthopaedic surgeons in Jordan collected data on demographics, offspring sex, fluoroscopy exposure, and compliance in using radiation protection. Participants reported 260 children, of whom 123 were male 47.3% and 137 were female 52.7%. No significant association was found between offspring sex ratio and weekly fluoroscopy exposure (P value = 0.25), or the use of radiation protection measures (P value 0.2). Although adherence to protective equipment varied, these behaviours showed no measurable reproductive effect. The study concludes that orthopaedic surgeons in Jordan have a slightly higher proportion of female children but this was not related to the occupational exposure, while the high rate of inadequate radiation safety compliance remains a notable occupational concern